2014
DOI: 10.1186/s12863-014-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of a threatened butterfly: comparison of allozymes, RAPDs and microsatellites

Abstract: BackgroundAddressing genetic issues in the management of fragmented wild populations of threatened species is one of the most important challenges in conservation biology. Nowadays, a diverse array of molecular methods exists to assess genetic diversity and differentiation of wild populations such as allozymes, dominant markers and co-dominant markers. However it remains worthwhile i) to compare the genetic estimates obtained using those several markers in order to ii) test their relative utility, reliability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
3
12
0
Order By: Relevance
“…This finding warns against the extrapolation of N e /N ratios, as different populations of the same species are likely to experience differences in the aforementioned factors. Ours are likely the first N e /N values reported in any moth and are quite similar to the ones published for wild populations of endangered butterflies by Saarinen et al (2010) and Turlure et al (2014).…”
Section: Implications For Conservationsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding warns against the extrapolation of N e /N ratios, as different populations of the same species are likely to experience differences in the aforementioned factors. Ours are likely the first N e /N values reported in any moth and are quite similar to the ones published for wild populations of endangered butterflies by Saarinen et al (2010) and Turlure et al (2014).…”
Section: Implications For Conservationsupporting
confidence: 88%
“…These authors suggested the incorporation of uncertainty into N e /N estimates. Ours are likely the first N e /N values reported in any moth and are quite similar to the ones published for wild populations of endangered butterflies by Saarinen et al (2010) and Turlure et al (2014). Using N e(SS) and N e(T) ( Table 4) and following Belmar-Lucero et al (2012), we obtain that the N e /N ratio is 1.1-5.4 times higher in Puebla (0.025, 0.033) than in the National Park (0.024, 0.006).…”
Section: Implications For Conservationsupporting
confidence: 88%
“…However, samples from the posterior distribution can be obtained using a Gibbs sampler. We used the BGLR software ( Pérez and de los Campos 2014 ) to draw samples from the posterior distribution of the above model.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this method demands fewer experimental steps and is relatively easy to perform. The use of dominant markers can be considered worthwhile in organisms for which no genomic information are available [48] as is the case for many butterfly species [49]. In addition, microsatellites are inherently difficult to use in butterflies, partially due to the high frequency of null alleles [49].…”
Section: Issr-pcr Amplificationmentioning
confidence: 99%
“…In addition, microsatellites are inherently difficult to use in butterflies, partially due to the high frequency of null alleles [49]. Therefore, ISSR genetic markers have been widely applied in studies on butterfly population genetic [15][16][17]43,48,[50][51][52][53][54][55][56][57].…”
Section: Issr-pcr Amplificationmentioning
confidence: 99%